Kajian Integrasi Antar Moda Transportasi Umum Pada Kawasan Pasar KM 5 Kota Palembang - Muhammad Rizka Fadli Wibowo; Melawaty Agustien; Edi Kadarsa (Jurnal Serambi Engineering, 2023)
Pasar KM 5 Palembang is a retail maket located on the national road and is passed by LRT and Angkot. The limited parking space creates congestion. Problems can be solved by improving the integration between good modes of transportation, This journal will obtain the results of an analysis of the integration between modes of public transportation in Pasar KM 5 Palembang in terms of socio-economic and travel characteristics of market visitors, conditions of physical and operational integration of public transportation and to obtain the results of intermodal integration. Data collection was carried out with questionnaire, which will be analyzed using GAP method to determine the difference between the performance of services in the field with applicable standards and community needs. It was found that the percentage value of motorcycle users was much greater than that of other transportation. In fact, the operational integration condition of the LRT transportation mode is quite good, although the physical integration condition still needs to be improved. The results of analysis of service performance between modes of transportation also show that the connectivity between the physical facilities of the mode to the Pasar KM 5 Palembang has not met expectations and needs to be improved.